Femicide as an extreme form of gender-based violence: Criminal profiling and prevention efforts in Indonesia - Anggi Pramita; Duta Nurdibyanandaru; Ike Herdiana; Arofi Kurniawan; Ramadhan Hardani Putra (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2026)
Femicide is the most extreme form of gender-based violence, rooted in unequal power relations, sexism, and patriarchal culture. This study examines how Indonesian cultural contexts may contribute to femicide and identifies patterns of motives, risk factors, and perpetrator characteristics through a criminal profiling perspective. This research employed a descriptive qualitative design based on a literature review. A nomothetic approach was used to identify general patterns among femicide perpetrators. The findings show that femicide in Indonesia is largely associated with intimate partner violence, with common motives including jealousy, possessiveness, and a desire for control. The identified risk factors include perpetrator characteristics such as age, employment status, and prior history of violence; victim vulnerabilities such as age and economic dependence; and abusive relationship dynamics. Patriarchal values and certain social norms may also reinforce the justification of extreme violence, including honour killings. The study highlights the importance of integrating criminal profiling into femicide prevention strategies through early intervention, stronger law enforcement, and gender-responsive policies aimed at protecting women.